PATIENT'S CHEST DISCOMFORT ASSOCIATED WITH DELAY IN REPERFUSION THERAPY ACUTE CORONARY SYNDROME - Elizabeth Yun Yun Vinsur; Djanggan Sargowo; Tony Suharsono (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2018)
Â Acute Coronary Syndrome (ACS) is a group of symptoms that are classify as unstable angina (ATS), ST-Segment Elevation Myocardial Infarction (STEMI) and non ST-Segment Elevation Myocardial Infarction (NSTEMI). Main objective to provide timely reperfusion therapy is essential to improve survival. Initial and rapid intervention after the occurrence of coronary artery disease is associated with better clinical outcomes, but it is hampered by the nature of the patient's seeking decisions Patients expect the type of heart attack they often see in medical movies and television: like chest pain that grips and causes it to fall to the floor. This study aims to analyze the chest discomfort experienced by patients associated with delay in reperfusion therapy of Acute Coronary Syndrome. The method used is observational analytic with cross sectional approach. Nonprobability sampling with time quota technique obtained sample of 60 respondents. The results obtained as many as 55% of patients come more than 120 minutes after the onset of discomfort in the chest. The patient's delay in coming to the associated hospital is an accompanying symptom factor at onset with p = 0.048, and OR = 4.596 (1.014-20.828). There were no significant differences in the scores of knowledge, behavior, and beliefs based on the ACS response index between patients who came <120 minutes and> 120 minutes. The conclusions of this study present the accompanying symptom presentations at onset with the time interval between the appearances of the SKA symptoms until arriving at the IGD door. Seeing the results of this study suggests the need for efforts from medical staff to optimize the interpretation of